2019
DOI: 10.17113/ftb.57.03.19.6035
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Lipid Hybrid Microparticles as Efficient Vehicles for Enhanced Stability and Bioaccessibility of Curcumin

Abstract: SUMMARYCurcumin is an active ingredient with multiple functions, but its application is often restricted due to its poor water solubility, weak stability, and consequently low bioaccessibility. Based on this, the aim of this work is to develop a new vehicle to overcome these restrictions. Here we developed a curcumin-loaded nanoemulsion and then curcumin-loaded silica-lipid hybrid microparticles through emulsification and vacuum drying, respectively. The loading of curcumin in the nanoemulsion and microparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In vitro simulated digestion tests have shown that curcumin-loaded nanoemulsions and SLH microparticles exhibit enhanced bioaccessibility compared to the control group. Moreover, SLH microparticles have demonstrated consistent storage stability across different temperatures over a period of six weeks [123]. Furthermore, innovative super-saturated SLH (super-SLH) formulations can increase drug loading capacity in cases of compounds having low potency [124].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro simulated digestion tests have shown that curcumin-loaded nanoemulsions and SLH microparticles exhibit enhanced bioaccessibility compared to the control group. Moreover, SLH microparticles have demonstrated consistent storage stability across different temperatures over a period of six weeks [123]. Furthermore, innovative super-saturated SLH (super-SLH) formulations can increase drug loading capacity in cases of compounds having low potency [124].…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro release data of the drug were fitted with the zero-order release equation, the first-order release equation and the Higuchi equation (Ma et al. 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The major reason contributing to the rapid metabolism is the poor stability of all Cur metabolites (Ma et al. 2019 ; Slika and Patra 2020 ). Therefore, Cur usually requires frequent dosing.…”
Section: Introductionmentioning
confidence: 99%
“…The CCK‐8 method was adopted to measure the cytotoxicity of effervescent tablets containing astaxanthin‐loaded microcapsules to L929 murine fibroblast cells. [ 35 ] L929 cells were provided by the Type Culture Collection of the Chinese Academy of Sciences (Shanghai, China). Cells were incubated in a DMEM culture medium with 10% FBS and 1% penicillin‐streptomycin in a 5% CO 2 cell incubator at 37 °C.…”
Section: Methodsmentioning
confidence: 99%